Effect of SGLT2 Inhibitors on Type 2 Diabetes Mellitus With Non-Alcoholic Fatty Liver Disease: A Meta-Analysis of Randomized Controlled Trials - Wei, Qiong; Xu, Xinyue; Guo, Li; Li, Jia; Li, Ling (Frontiers in Endocrinology, 2021)
Objective: Clinical trials showed that sodium-glucose cotransporter 2 (SGLT2) inhibitors can improve non-alcoholic fatty liver disease (NAFLD). In this work, a meta-analysis of randomized controlled trials was conducted to evaluate the effect of SGLT2 inhibitors on type 2 diabetes mellitus (T2DM) with NAFLD. Methods: PubMed, Embase, Web of Science, and Cochrane Libraries were used for the systematic literature review to determine eligible studies. A randomized effect model was adapted to perform a meta-analysis on these eligible studies to estimate the combined effect sizes. Differences were expressed as the weighted average difference (WMD) of the continuous results and the 95% confidence interval (CI). Results: Ten randomized controlled trials with 573 participants were included. SGLT2 inhibitors significantly reduced the levels of alanine transaminase (WMD -4.87 [95% CI: -8.32, -1.41], p = 0.006) and aspartate aminotransferase (WMD -2.56 [95% CI: -3.83, -1.29], p <0.0001). In terms of body composition, liver proton density fat fraction (WMD -2.20 [95% CI: -3.67, -0.74], p = 0.003), visceral fat mass area (WMD -20.71 [95% CI: -28.19, -13.23], p <0.00001), subcutaneous fat areas (WMD -14.68 [95% CI: -26.96, -2.40], p = 0.02) were also significantly reduced. Conclusion: SGLT2 inhibitors can remarkably reduce hepatic enzyme and hepatic fat and improve body composition and thus may become a new treatment option for NAFLD.